Разработка генетического алгоритма в контексте оценки научно-инновационных проектов. Development of genetic algorithm in the context of the assessment of scientific and innovative projects. (ҚазҰУ Хабаршысы. Математика, механика, информатика сериясы, 2013)
Предложен генетический алгоритм, позволяющий производить отбор научно инновационных проектов. Представлена функция приспособленности, которая численно характеризует научно инновационный проект. Введено понятие индекса привлекательности проекта. Описаны результаты лабораторных экспериментов, направленных на принятие решений при оценке научно-инновационных проектов. Установлено, что рассмотрение научно-инновационных проектов как особей существенно способствует улучшению результата их отбора, а также оптимизирует процесс оценки и выбора проектов.The genetic algorithm, allowing making selection of scientific and innovative projects is offered. Fitness function which numeric characterizes the scientific and innovative project is presented. The concept of an index of attractiveness of the project is entered. Resultsof the laboratory experiments directed on decision-making at an assessment of scientific and innovative projects are described. It is established that consideration of scientific and innovative projects as individuals significantly promotes improvement of result of selectionand optimizes process of an assessment and a choice of projects.